Taxation and entrepreneurship - Pertti Haaparanta; Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2001)
The paper analyses the impacts of occupational choice and entrepreneurial effort on the structure of wage, profit and capital taxation. Entrepreneurial effort is unobservable and therefore not tax-deductible. The optimal profit tax is less than unity even if individual entrepreneurial effort is fixed. It decreases with the sufficiently adverse effects on the number of firms. With the optimal setting of wage and profit taxes entrepreneurial effort has ambiguous effect on the optimal profit tax level. Because of the possible opposite effects of the adjustment in the number of firms and entrepreneurial effort, information on aggregate entrepreneurial effort is not enough in the setting of the optimal tax policy. It is also shown that the optimal setting of wage taxes is different when profit taxation is arbitrarily low. This leads to the setting of wage taxes at too high a level. The reason is that lower entrepreneurial effort owing to severe wage taxes also raises the wage tax base. – – Tutkimus tarkastelee ammattivalinnan ja yrittäjäpanoksen vaikutusta palkka-, yritys- ja pääomaverotukseen. Yrittäjäpanos ei ole havaittava tuotantopanos eikä verotuksessa vähennyskelpoinen. Tästä syystä optimaalinen yritysverotus on vähemmän kuin 100 prosenttia vaikka yrittäjäpanos olisi joustamaton verotuksen tasolle. Optimaalinen yritysverotus alenee kun yritysvero vähentää yrittäjien määrää riittävän paljon. Kun sekä palkka- ja yritysverotus asetetaan optimaalisesti, yritysverotus voi sen sijaan eräissä tapauksissa kiristyä, kun yritysvero vähentää yrittäjäpanosta. Optimaaliseen yritysverotukseen vaikuttaa siten olennaisesti sekä yrittäjien määrä että kunkin yrittäjän panostus. Tutkimuksessa osoitetaan myös, että optimaalinen palkkaverotus muuttuu olennaisesti silloin, kun yritysverotus on liian keveätä. Tälloin palkkaverotuksen taso muodostuu korkeaksi. Syynä tähän on se, että myös yrittäjäpanoksen väheneminen kireän palkkaverotuksen myötä nostaa palkkoja ja palkkaveropohjaa. Optimaalisessa verotuksessa palkkaverotus sen sijaan aina alenee mitä negatiivisemmat vaikutukset veroilla on yrittäjäpanokseen.
Keywords: M13; H21; H25; J62; 330; optimal taxation; occupational choice; entrepreneurship; self-employment; Berufswahl; Entrepreneurship-Ansatz; Selbstständige; Steuerpolitik; Kleines-offenes-Land; Theorie